Mortality in Salmon ( Salmo salar ) Fry Related to Lipoid Liver Disease Induced by Unbalanced Fatty Acid Composition of the Diet - Caroline Ek; Lo Persson; Charlotte Axén (Journal of Fish Diseases, 2026)
In 2023, all but one Swedish restocking farm rearing Baltic salmon and sea trout fry experienced massive mortality caused by lipoid liver disease (LLD). The struck farms used the same feed, and this was suspected to be the cause of the outbreak. We performed two parallel feed trials in three salmon populations as well as fatty acid and antioxidant analyses of feed and fish to investigate the causal relationship between the feed and the LLD mortality. Significant mortality was induced in one population and LLD histopathology was induced in all three populations in groups fed the suspected feed (test feed) but not in the control groups, linking the test feed to the outbreak in 2023. Fatty acid analysis revealed a difference in bound fatty acid composition between the suspected feed and the control feeds, including higher amounts of erucic acid. Erucic acid has negative health effects for fish by altering lipid metabolism. It is present in for example, capelin, a main ingredient in this feed. The test feed also contained lower levels of several antioxidants, especially vitamin A. Antioxidative status of the fish could not be fully analysed but results indicated a difference in antioxidative status between the populations.